PROMOTING STUDENTS’ SPEAKING ABILITY THROUGH ROLE PLAY WITHIN DICOURSE BASED APPROACH - Lilik Handayani (Institut Teknologi Sepuluh Nopember, 2013)
In teaching English for engineering students, the emphasis goes to understanding the technical terms within reading scientific texts, writing technical report, and speaking on certain topics relevant to the major specialization. Students of Shipbuilding Institute of Polytechnic Surabaya (SHIPS) are demanded to be able to communicate actively either in oral or written English particularly after graduation when they work in offshore, mining and shipyard industries.Therefore, this study is aimed to promote students’ speaking ability through role play within discourse based approach. Role play is selected to develop students’ knowledge about why, how and when to communicate based on the real-life context and their specialized background. Students are encouraged to act out the roles with a partner in speaking tasks. A continuum of spoken texts in English are provided to explore students macro and micro-level discourse awareness. This paper elaborates the stages of designing speaking tasks focusing on role play.